2012
DOI: 10.1111/j.1532-950x.2012.01067.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ventral Slot Procedure on Spinal Cord Compression in Dogs with Single Static Intervertebral Disc Disease: Preliminary Findings while Evaluating a Semiquantitative Computed Tomographic Myelographic Score of Spinal Cord Compression

Abstract: VS improves neurologic function but often fails at completely resolving extradural SCC. The proposed CT myelographic score is highly reliable, assuring consistency among and within observers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 19 publications
1
18
0
1
Order By: Relevance
“…7 Even if mild-tomoderate bleeding usually has no clinical significance, it can affect the surgeon's vision, requiring pausing of the decompression procedure, and increasing the anesthesia time and the risk of complications. 17,23 Both primary surgeons participating in our study found that performing ventral slot surgery with VITOM TM system allowed better control of sinus bleeding.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…7 Even if mild-tomoderate bleeding usually has no clinical significance, it can affect the surgeon's vision, requiring pausing of the decompression procedure, and increasing the anesthesia time and the risk of complications. 17,23 Both primary surgeons participating in our study found that performing ventral slot surgery with VITOM TM system allowed better control of sinus bleeding.…”
Section: Discussionmentioning
confidence: 82%
“…Surgical loupes, the endoscope, and the operative microscope may also prevent the second surgeon from playing a more active role during the surgical procedure. Moreover, the endoscope and the operative microscope are considered to have steep learning curves …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations